2020
DOI: 10.1039/c9ra08600e
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted Article: Overexpression of circ_0034642 contributes to hypoxia-induced glycolysis, cell proliferation, migration and invasion in gliomas by facilitating TAGLN2 expression via sponging miR-625-5p

Abstract: Circ_0034642 was upregulated under hypoxic conditions in gliomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Neutrophils (NE) increase in production and release inflammatory factors during the inflammatory process (15). Previous studies have suggested that hypoxia, a common feature of solid tumors, targets multiple cell types in the tumor microenvironment including neutrophils by regulating the expression of multiple angiogenic genes (16)(17)(18). Expression of the immunosuppressive cytokine TGF-β is upregulated in tumors and plays a significant role in blocking immune responses and affecting tumor progression.…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophils (NE) increase in production and release inflammatory factors during the inflammatory process (15). Previous studies have suggested that hypoxia, a common feature of solid tumors, targets multiple cell types in the tumor microenvironment including neutrophils by regulating the expression of multiple angiogenic genes (16)(17)(18). Expression of the immunosuppressive cytokine TGF-β is upregulated in tumors and plays a significant role in blocking immune responses and affecting tumor progression.…”
Section: Introductionmentioning
confidence: 99%